Language, Heart, and Mind Studies at the intersection of emotion and cognition - Bogucki, Lukasz; Bogucki, Lukasz (Peter Lang, 2020)
A major premise of this book is that language use is critically conditioned by affective content and cognitive factors rather than being a case of objective computation and manipulation of structures. The 21 chapters of this book deals with how language interacts with emotion, and with mind and cognition, from both intralingual and cross-linguistic perspectives. The second major focus is the theoretical framework, best-suited for research relationships between language, cognition, and emotion as well as the effect that emotion has on the conceptualizer who constructs meanings based on language stimuli. Furthermore, the authors investigate how emotion and rational projections of events interact and what their consequences are in the conceptual world, media discourse, and translation.